Churchill's secret war the British empire and the ravaging of India during World War II - Mukerjee, Madhusree
Examines Winston Churchill's efforts to defeat the freedom movement in India during World War II, comparing his actions in Europe to the decisions he made between 1940 and 1944, which resulted in the deaths of more than three million men, women, and children in India.